Cost-effectiveness and sustainability of improved hospital oxygen systems in Nigeria. Issue 8 (10th August 2022) - Graham, Hamish R; Bakare, Ayobami A; Ayede, Adejumoke Idowu; Eleyinmi, Joseph; Olatunde, Oyaniyi; Bakare, Oluwabunmi R; Edunwale, Blessing; Neal, Eleanor F G; Qazi, Shamim; McPake, Barbara; Peel, David; Gray, Amy Z; et al.
Abstract : Introduction: Improving hospital oxygen systems can improve quality of care and reduce mortality for children, but we lack data on cost-effectiveness or sustainability. This study evaluated medium-term sustainability and cost-effectiveness of the Nigeria Oxygen Implementation programme. Methods: Prospective follow-up of a stepped-wedge trial involving 12 secondary-level hospitals. Cross-sectional facility assessment, clinical audit (January–March 2021), summary admission data (January 2018–December 2020), programme cost data. Intervention: pulse oximetry introduction followed by solar-powered oxygen system installation with clinical and technical training and support. Primary outcomes: (i) proportion of children screened with pulse oximetry; (ii) proportion of hypoxaemic (SpO2 <90%) children who received oxygen. Comparison across three time periods: preintervention (2014–2015), intervention (2016–2017) and follow-up (2018–2020) using mixed-effects logistic regression. Calculated cost-effectiveness of the intervention on child pneumonia mortality using programme costs, recorded deaths and estimated counterfactual deaths using effectiveness estimates from our effectiveness study. Reported cost-effectiveness over the original 2-year intervention period (2016–2017) and extrapolated over 5 years (2016–2020). Results: Pulse oximetry coverage for neonates and children remained high during follow-up (83% and 81%) compared with full oxygen system period (94% and 92%) and preintervention (3.9% and 2.9%). Oxygen coverage for hypoxaemic neonates/children was similarly high (94%/88%) compared with full oxygen system period (90%/82%). Functional oxygen sources were present in 11/12 (92%) paediatric areas and all (8/8) neonatal areas; three-quarters (15/20) of wards had a functional oximeter. Of 32 concentrators deployed, 23/32 (72%) passed technical testing and usage was high (median 10 797 hours). Estimated 5-year cost-effectiveness US86 per patient treated, 2694–4382 per life saved and 82–125 per disability-adjusted life year-averted. We identified practical issues for hospitals and Ministries of Health wishing to adapt and scale up pulse oximetry and oxygen. Conclusion: Hospital-level improvements to oxygen and pulse oximetry systems in Nigerian hospitals have been sustained over the medium-term and are a highly cost-effective child pneumonia intervention.